Method for manufacturing adhesive sheets for semiconductor processing and semiconductor devices

JP7936686B2Active Publication Date: 2026-10-16LINTEC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022117946
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-27
Filing Date
2022-07-25
Publication Date
2026-10-16
Estimated Expiration
2042-07-25

AI Technical Summary

Benefits of technology

【0014】 本発明によると、研削屑の付着量が低減され、搬送性に優れる半導体加工用粘着シート及び該半導体加工用粘着シートを用いる半導体装置の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007936686000001
    Figure 0007936686000001
  • Figure 0007936686000002
    Figure 0007936686000002
  • Figure 0007936686000003
    Figure 0007936686000003
Patent Text Reader

Abstract

To provide an adhesive sheet for semiconductor processing with reduced adhesion of grinding debris and excellent transportability, and a method for manufacturing a semiconductor device using the adhesive sheet for semiconductor processing.SOLUTION: Provided are an adhesive sheet for semiconductor processing comprising, in this order, a surface coat layer, a buffer layer, a base material and an adhesive layer, wherein the surface coat layer has a static friction coefficient against SUS304 of 0.70 or less, and a method for manufacturing a semiconductor device using the adhesive sheet for semiconductor processing.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to an adhesive sheet for semiconductor processing and a method for manufacturing a semiconductor device. [Background technology]

[0002] As information terminal devices become thinner, smaller, and more multifunctional at an accelerating pace, the semiconductor devices installed in these devices are also required to be thinner and more densely packed. One method used to thin semiconductor devices has been to grind the back surface of the semiconductor wafer used in the semiconductor device. Back surface grinding of a semiconductor wafer is performed by attaching an adhesive sheet for back surface grinding (hereinafter also called a "back grind sheet") to the surface of the semiconductor wafer, and protecting the surface of the semiconductor wafer with this sheet. The back grind sheet is peeled off and removed from the surface of the semiconductor wafer after back surface grinding.

[0003] In recent years, pre-dicing and stealth pre-dicing methods have been put into practical use as grinding and dicing methods that can thin semiconductor chips while suppressing damage to them. The pre-dicing method is a method in which grooves of a predetermined depth are formed on the surface of a semiconductor wafer with a dicing blade or the like, and then the semiconductor wafer is ground from the back side down to the grooves to dicate it into semiconductor chips. The stealth pre-dicing method is a method in which a modified region is formed inside the semiconductor wafer by irradiation with laser light, and then the semiconductor wafer is ground from the back side, and the modified region is used as the starting point for splitting to dicate it into semiconductor chips. In these methods as well, a backgrind sheet is used to protect the surface of the semiconductor wafer.

[0004] Along with the development of these thinning process technologies, backgrind sheets are also required to have functions that enable the thinning of semiconductor chips with good yield, and various studies are being conducted. Patent Document 1 discloses an adhesive sheet for protecting the surface of a semiconductor wafer, applicable to a pre-dicing method or a stealth pre-dicing method, comprising a base film, an intermediate layer made of an adhesive and provided on at least one side of the base film, and an outermost adhesive layer provided on the outermost layer opposite the base film of the intermediate layer, wherein the intermediate layer is made of a material that hardens by a curing treatment after the adhesive sheet is formed. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2015-56446 [Overview of the Initiative] [Problems that the invention aims to solve]

[0006] According to the adhesive sheet for protecting the surface of a semiconductor wafer described in Patent Document 1, it is possible to suppress kerf shift, which occurs when the original chip spacing is disrupted after the semiconductor wafer has been separated into individual chips, to suppress contamination of the semiconductor wafer by grinding debris, and to prevent adhesive residue from remaining on the chips when the surface protection tape is peeled off.

[0007] Incidentally, when performing backside grinding, the backgrind sheet attached to the semiconductor wafer is fixed on the side opposite to the side attached to the semiconductor wafer (hereinafter also referred to as the "backside") by a support device such as a chuck table. The semiconductor wafer, fixed on the table of the support device via the backgrind sheet, is then ground on its backside while cooling water is supplied to the grinding surface to remove heat generated by grinding and grinding debris.

[0008] When performing backside grinding, if grinding debris is present between the backgrind sheet and the support table, cracks may occur in the semiconductor wafer or semiconductor chip due to the impact when fixing the semiconductor wafer to the table, the pressure and vibration during backside grinding, etc., starting from the area where the grinding debris is present. Since the grinding debris adheres to the back surface of the backgrind sheet while contained in the cooling water, it is necessary to reduce the amount of grinding debris adhering to the back surface of the backgrind sheet in order to suppress the occurrence of the above cracks.

[0009] Furthermore, while cooling water is supplied to remove frictional heat generated during semiconductor wafer grinding, it is difficult to completely remove the frictional heat, and the temperature of the backgrind sheet that holds the semiconductor wafer rises to some extent. In other words, the backgrind sheet is heated for a certain period of time under pressure against a support device such as a chuck table during semiconductor wafer grinding, which can cause the backgrind sheet to adhere excessively to the support device. After grinding, the semiconductor wafer needs to be lifted from the support device by a transport arm or the like and transported for the next process, but if the backgrind sheet adheres excessively to the support device, the lifting may fail, and the wafer may not be able to be transported. This problem tends to be particularly apparent when using a backgrind sheet with reduced grinding debris adhesion on the back surface.

[0010] The adhesive sheet for protecting the surface of a semiconductor wafer described in Patent Document 1 did not adequately meet the requirements for reducing the amount of grinding debris adhering to the back surface of the back grind sheet and improving its transportability.

[0011] This invention has been made in view of the above circumstances, and aims to provide an adhesive sheet for semiconductor processing that reduces the amount of grinding debris adhering to it and has excellent transportability, and a method for manufacturing a semiconductor device using the semiconductor processing adhesive sheet. [Means for solving the problem]

[0012] As a result of diligent research, the inventors of the present invention have found that the above problems can be solved by an adhesive sheet for semiconductor processing having a surface coating layer, a buffer layer, a substrate, and an adhesive layer in that order, with static friction coefficients within a specific range, and have completed the present invention described below.

[0013] In other words, the present invention relates to the following [1] to

[11] . [1] The surface coating layer, buffer layer, substrate and adhesive layer are provided in this order. The aforementioned surface coating layer is an adhesive sheet for semiconductor processing, having a static friction coefficient of 0.70 or less with respect to SUS304. [2] The semiconductor processing adhesive sheet according to [1] above, wherein the surface coating layer is a layer formed from a surface coating layer forming composition containing a resin component and a slipperiness improving component. [3] The adhesive sheet for semiconductor processing according to [2] above, wherein the resin component has a heteroatom content of 7% by mass or less. [4] The semiconductor processing adhesive sheet according to [2] or [3] above, wherein the content of the resin component in the surface coating layer forming composition is 50 to 99% by mass relative to the total amount (100% by mass) of the active ingredients of the surface coating layer forming composition. [5] The adhesive sheet for semiconductor processing according to any one of [2] to [4] above, wherein the slipperiness-improving component has a heteroatom content of 30% by mass or more. [6] The semiconductor processing adhesive sheet according to any one of [2] to [5] above, wherein the content of the slipperiness-improving component in the surface coating layer forming composition is 0.1 to 30% by mass relative to the total amount (100% by mass) of the active ingredients in the surface coating layer forming composition. [7] The semiconductor processing adhesive sheet according to any of [1] to [6] above, wherein the thickness of the surface coating layer is 0.05 to 10 μm. [8] The semiconductor processing adhesive sheet according to any one of [1] to [7] above, wherein the buffer layer is formed from a buffer layer forming composition containing urethane (meth)acrylate. [9] An adhesive sheet for semiconductor processing described in any of [1] to [8] above, used for grinding the back surface of a semiconductor wafer.

[10] A step of affixing the pressure-sensitive adhesive sheet for semiconductor processing according to any one of the above [1] to [9] to the surface of a semiconductor wafer with the pressure-sensitive adhesive layer as the affixing surface, A step of grinding the back surface of the semiconductor wafer in a state where the surface coat layer side of the pressure-sensitive adhesive sheet for semiconductor processing affixed to the semiconductor wafer is fixed by a supporting device, A method for manufacturing a semiconductor device, comprising:

[11] A dividing scheduled line forming step, which is step a of forming grooves on the surface of a semiconductor wafer, or step b of forming a modified region inside the semiconductor wafer from the front surface or back surface of the semiconductor wafer, A sheet affixing step of, after the step a, or before or after the step b, affixing the pressure-sensitive adhesive sheet for semiconductor processing according to any one of the above [1] to [9] to the surface of the semiconductor wafer with the pressure-sensitive adhesive layer as the affixing surface, A grinding and singulation step of, in a state where the surface coat layer side of the pressure-sensitive adhesive sheet for semiconductor processing affixed to the semiconductor wafer is fixed by a supporting device, grinding the back surface of the semiconductor wafer to singulate the semiconductor wafer into a plurality of semiconductor chips starting from the grooves or the modified regions, The method for manufacturing a semiconductor device according to the above

[10] , comprising: [Effects of the Invention]

[0014] According to the present invention, it is possible to provide a pressure-sensitive adhesive sheet for semiconductor processing that has a reduced amount of attached grinding debris and excellent transportability, and a method for manufacturing a semiconductor device using the pressure-sensitive adhesive sheet for semiconductor processing. [Modes for Carrying Out the Invention]

[0015] In the present specification, for preferred numerical ranges, the lower limit values and upper limit values described stepwise can be independently combined with each other. For example, from the description "preferably 10 to 90, more preferably 30 to 60", the "preferred lower limit value (10)" and the "more preferred upper limit value (60)" can be combined to make "10 to 60".

[0016] In the present specification, for example, the term "(meth)acrylic acid" refers to both "acrylic acid" and "methacrylic acid", and the same applies to other similar terms.

[0017] In the present specification, "energy ray" means an electromagnetic wave or a charged particle beam that has an energy quantum, and examples thereof include ultraviolet rays, radiation, electron beams, and the like. Ultraviolet rays can be irradiated by using, for example, an electrodeless lamp, a high-pressure mercury lamp, a metal halide lamp, a UV-LED or the like as an ultraviolet source. Electron beams can be irradiated with those generated by an electron beam accelerator or the like. In the present specification, "energy ray polymerizable" means the property of polymerizing upon irradiation with an energy ray. Further, "energy ray curable" means the property of curing upon irradiation with an energy ray, and "non-energy ray curable" means the property of not having energy ray curability.

[0018] In the present specification, the "front surface" of a semiconductor wafer refers to the surface on which circuits are formed, and the "back surface" refers to the surface on which no circuits are formed.

[0019] The mechanism of action described in the present specification is a speculation, and does not limit the mechanism by which the effect of the pressure-sensitive adhesive sheet for semiconductor processing of the present invention is achieved.

[0020] [Pressure-sensitive adhesive sheet for semiconductor processing] The pressure-sensitive adhesive sheet for semiconductor processing of the present embodiment (hereinafter also referred to as "pressure-sensitive adhesive sheet") has a surface coat layer, a buffer layer, a base material and a pressure-sensitive adhesive layer in this order, and the surface coat layer is a pressure-sensitive adhesive sheet for semiconductor processing having a static friction coefficient of 0.70 or less with respect to SUS304. The pressure-sensitive adhesive sheet of the present embodiment is attached to the front surface of a semiconductor device which is a workpiece, and is used for performing predetermined processing on the semiconductor device while protecting the front surface. After the predetermined processing is performed on the workpiece, the pressure-sensitive adhesive sheet of the present embodiment is peeled and removed from the semiconductor device. In this embodiment, "semiconductor device" refers to any device that can function by utilizing semiconductor properties, such as semiconductor wafers, semiconductor chips, electronic components including said semiconductor chips, and electronic devices equipped with said electronic components. Among these, the adhesive sheet of this embodiment is suitable for processing semiconductor wafers.

[0021] The adhesive sheet of this embodiment may or may not have layers other than the surface coating layer, buffer layer, substrate, and adhesive layer. Examples of layers other than the substrate and adhesive layer include an intermediate layer provided between the substrate and the adhesive layer, and a release sheet provided on the side of the adhesive layer opposite to the substrate. The following describes each component that makes up the adhesive sheet of this embodiment.

[0022] <Surface coating layer> The surface coating layer is a layer provided on the side opposite to the substrate of the buffer layer, and is fixed by a support device when processing semiconductor devices.

[0023] (Static friction coefficient) The static friction coefficient of the surface coating layer of the adhesive sheet in this embodiment with respect to SUS304 is 0.70 or less. The adhesive sheet of this embodiment has a static friction coefficient of 0.70 or less with respect to the SUS304 surface coating layer, which reduces the amount of grinding debris adhering to it and also provides excellent transportability. The reason for this is not entirely clear, but it is presumed that a surface coating layer with a static friction coefficient of 0.70 or less is less susceptible to water containing grinding debris adhering to it, and also suppresses excessive adhesion to support devices and the like. From the above viewpoint, the static friction coefficient of the surface coating layer of the adhesive sheet of this embodiment with respect to SUS304 is preferably 0.60 or less, more preferably 0.50 or less. On the other hand, the lower limit of the static friction coefficient of the surface coating layer of the adhesive sheet of this embodiment with respect to SUS304 is not particularly limited, but from the viewpoint of ease of manufacture, for example, it may be 0.01 or more, 0.10 or more, or 0.20 or more. The static friction coefficient of the surface coating layer with respect to SUS304 is a value measured in accordance with JIS K 7125:1999, and can be measured specifically by the method described in the examples.

[0024] The surface coating layer of the adhesive sheet in this embodiment is preferably formed from a surface coating layer forming composition containing a resin component and a slipperiness-improving component.

[0025] (Resin components) As for the resin component, thermoplastic resins are preferred, and polyolefin resins are more preferred, from the viewpoint of reducing the amount of grinding debris adhering to the surface.

[0026] [Polyolefin resins] By including a polyolefin resin in the surface coating layer formation composition, the surface coating layer of the adhesive sheet in this embodiment tends to reduce the amount of grinding debris adhering to it.

[0027] Polyolefin resins are resins obtained by polymerizing monomers that contain at least an olefin. Here, "polyolefin resin" in this embodiment means either a resin obtained by homopolymerizing an olefin, or a resin obtained by copolymerizing an olefin with a monomer other than an olefin, which contains 50% by mass or more of constituent units derived from an olefin. Furthermore, in this embodiment, "olefin" means an unsaturated hydrocarbon having an ethylenically unsaturated bond, and compounds containing heteroatoms are not included in "olefin" in this embodiment. In this specification, "heteroatom" means all atoms other than carbon atoms and hydrogen atoms. Furthermore, in the following explanation, groups containing ethylenically unsaturated bonds may be simply referred to as "unsaturated groups." Polyolefin resins may be used individually or in combination of two or more types.

[0028] The content of olefin-derived structural units in the polyolefin resin is not particularly limited, but is preferably 70% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more. When the content of olefin-derived structural units in the polyolefin resin is above the above lower limit, the amount of grinding debris adhering tends to be further reduced. Furthermore, the content of constituent units derived from olefins in the polyolefin resin may be 100% by mass, but it may be 99.5% by mass or less, or 99% by mass or less, in order to include constituent units derived from monomers other than olefins for the purpose of improving solvent solubility, etc.

[0029] Examples of olefins that make up polyolefin resins include linear olefins, cyclic olefins, and aromatic vinyl compounds. The olefins that make up the polyolefin resin may be used individually or in combination of two or more types.

[0030] Examples of chain-like olefins include chain-like monoolefins such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 2-methyl-1-propene, 3-methyl-1-pentene, 4-methyl-1-pentene, and 5-methyl-1-hexene; chain-like non-conjugated dienes such as 1,4-hexadiene, 4-methyl-1,4-hexadiene, and 5-methyl-1,4-hexadiene; and chain-like conjugated dienes such as 1,3-butadiene, isoprene, 1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, 2-phenyl-1,3-butadiene, and 1,3-hexadiene. Among these, chain-like olefins having 2 to 6 carbon atoms are preferred, and ethylene and propylene are more preferred.

[0031] Examples of cyclic olefins include cyclic monoolefins such as cyclobutene, cyclopentene, methylcyclopentene, cyclohexene, methylcyclohexene, cycloheptene, and cyclooctene; cyclic diolefins such as cyclohexadiene, methylcyclohexadiene, cyclooctadiene, methylcyclooctadiene, and phenylcyclooctadiene; and polycyclic olefins such as norbornene, dicyclopentadiene, tetracyclododecene, ethyltetracyclododecene, ethylidenetetracyclododecene, and tetracyclo[7.4.0.110,13.02,7]trideca-2,4,6,11-tetraene. Among these, tetracyclododecene is preferred from the viewpoint of improving solvent solubility and facilitating the formation of a surface coating layer by application.

[0032] Examples of aromatic vinyl compounds include styrene, o-methylstyrene, m-methylstyrene, and p-methylstyrene.

[0033] Examples of monomers other than olefins that may be copolymerized with olefins include monomers having an oxygen atom and an ethylenically unsaturated bond, and monomers having a nitrogen atom and an ethylenically unsaturated bond. Other monomers may be used individually or in combination of two or more.

[0034] Examples of monomers having an oxygen atom and an ethylenically unsaturated bond include acid anhydrides such as maleic anhydride, methyl maleic anhydride, dimethyl maleic anhydride, phenyl maleic anhydride, and diphenyl maleic anhydride; maleic acids such as maleic acid, methyl maleic acid, dimethyl maleate, diethyl maleate, dibutyl maleate, and monomethyl maleate; (meth)acrylic acids and (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cycloalkyl (meth)acrylate with 3 to 20 carbon atoms in the cycloalkyl group, benzyl (meth)acrylate, and isobornyl (meth)acrylate; and vinyl ester compounds such as vinyl acetate and vinyl propionate. Among these, acid anhydrides and vinyl ester compounds are preferred from the viewpoint of improving solvent solubility and facilitating the formation of a surface coating layer by application, maleic anhydride and vinyl acetate are more preferred, and maleic anhydride is even more preferred.

[0035] Examples of monomers having a nitrogen atom and an ethylenically unsaturated bond include maleimide compounds and their derivatives, and nitrile monomers. Examples of maleimide compounds and their derivatives include maleimides; N-alkyl-substituted maleimides such as N-methylmaleimide and N-ethylmaleimide; and N-aryl-substituted maleimides such as N-phenylmaleimide. Examples of nitrile monomers include acrylonitrile and methacrylonitrile.

[0036] Among the above constituent units, polyolefin resins are preferably made to contain constituent units derived from chain-like olefins having 2 to 6 carbon atoms (hereinafter also referred to as "chain-like olefin constituent units (A)"), from the viewpoint of further reducing the amount of grinding debris adhering to them, and are more preferably made to contain one or more selected from the group consisting of constituent units derived from ethylene and constituent units derived from propylene.

[0037] As for polyolefin resins, from the viewpoint of improving solvent solubility and facilitating the formation of a surface coating layer by application, it is preferable to have a polyolefin resin that contains a linear olefin-based structural unit (A) along with a structural unit derived from a monomer having an oxygen atom and an ethylenically unsaturated bond (hereinafter also referred to as "structural unit containing an oxygen atom (B)"), or a polyolefin resin that contains a linear olefin-based structural unit (A) along with a structural unit derived from an aromatic vinyl compound (hereinafter also referred to as "aromatic vinyl compound-based structural unit (C)").

[0038] When a polyolefin resin contains a chain-like olefin structural unit (A) and a structural unit (B) containing an oxygen atom, the content of the chain-like olefin structural unit (A) in the polyolefin resin is not particularly limited, but is preferably 80 to 99.5% by mass, more preferably 90 to 99% by mass, and even more preferably 95 to 98.8% by mass. When a polyolefin resin contains a chain-like olefin structural unit (A) and a structural unit (B) containing an oxygen atom, the content of the structural unit (B) containing an oxygen atom in the polyolefin resin is not particularly limited, but is preferably 0.5 to 20% by mass, more preferably 1 to 10% by mass, and even more preferably 1.2 to 5% by mass. When the content of the chain-like olefin-based structural unit (A) and the oxygen atom-containing structural unit (B) is within the above range, good solvent solubility is obtained while tending to further reduce the amount of grinding debris adhering to the material.

[0039] Examples of polyolefin resins containing chain-like olefin structural units (A) and structural units containing oxygen atoms (B) include binary copolymers such as ethylene-maleic anhydride copolymer, ethylene-vinyl acetate copolymer, ethylene-(meth)acrylate copolymer, propylene-maleic anhydride copolymer, propylene-vinyl acetate copolymer, and propylene-(meth)acrylate copolymer; ethylene-maleic anhydride-vinyl acetate copolymer, ethylene-maleic anhydride-(meth)acrylate copolymer, ethylene-vinyl acetate-(meth)acrylate copolymer, propylene-maleic anhydride-vinyl acetate copolymer, Examples include polypolymers such as propylene-maleic anhydride-(meth)acrylate copolymer, propylene-vinyl acetate-(meth)acrylate copolymer, ethylene-propylene-maleic anhydride copolymer, ethylene-propylene-vinyl acetate copolymer, ethylene-propylene-(meth)acrylate copolymer, ethylene-butene-maleic anhydride copolymer, ethylene-butene-vinyl acetate copolymer, ethylene-butene-(meth)acrylate copolymer, propylene-butene-maleic anhydride copolymer, propylene-butene-vinyl acetate copolymer, and propylene-butene-(meth)acrylate copolymer. Among these, propylene-butene-maleic anhydride copolymer is preferred from the viewpoint of further reducing the amount of grinding debris adhering to the surface and improving solvent solubility to facilitate the formation of a surface coating layer by application.

[0040] When a polyolefin resin contains a chain-like olefin structural unit (A) and an aromatic vinyl compound structural unit (C), the content of the chain-like olefin structural unit (A) in the polyolefin resin is not particularly limited, but is preferably 5 to 60% by mass, more preferably 10 to 50% by mass, and even more preferably 20 to 40% by mass. When a polyolefin resin contains a chain-like olefin structural unit (A) and an aromatic vinyl compound structural unit (C), the content of the aromatic vinyl compound structural unit (C) in the polyolefin resin is not particularly limited, but is preferably 40 to 95% by mass, more preferably 50 to 90% by mass, and even more preferably 60 to 80% by mass. When the content of the chain-like olefin-based structural unit (A) and the aromatic vinyl compound-based structural unit (C) is within the above range, good solvent solubility is obtained while tending to further reduce the amount of grinding debris adhering to the material.

[0041] Examples of polyolefin resins containing chain-like olefin structural units (A) and aromatic vinyl compound structural units (C) include hydrogenated styrene-butadiene-styrene block copolymers and hydrogenated styrene-isoprene-styrene block copolymers. Examples of hydrogenated styrene-butadiene-styrene block copolymers include SEBS, which is obtained by fully hydrogenating the carbon-carbon double bonds in the butadiene block, and SBBS, which is obtained by partially hydrogenating the carbon-carbon double bonds at the 1,2-bonding sites in the butadiene block. Among these, SEBS is preferred.

[0042] Other polyolefin resins may be used as long as they can form a surface coating layer. Examples of other polyolefin resins include polyolefin resins composed solely of chain-like olefin structural units (A) such as polyethylene, polypropylene, polybutadiene, ethylene-propylene copolymer, ethylene-butene copolymer, and propylene-butene copolymer; and polyolefin resins composed solely of aromatic vinyl compound structural units (C) such as polystyrene.

[0043] The surface coating layer forming composition may or may not contain resins other than polyolefin resins. The content of polyolefin resin in the resin component is preferably 90-100% by mass, more preferably 95-100% by mass, and even more preferably 98-100% by mass, from the viewpoint of further reducing the amount of grinding debris adhering to the resin and further improving transportability.

[0044] [Heteroatom content of resin components] The content of heteroatoms in the resin component is not particularly limited, but is preferably 7% by mass or less, more preferably 0.2 to 4% by mass, and even more preferably 0.5 to 1% by mass. When the heteroatom content in the resin component is below the upper limit mentioned above, the amount of grinding debris adhering to the surface tends to be further reduced. Conversely, when the heteroatom content in the resin component is above the lower limit mentioned above, the solvent solubility of the resin component improves, making it easier to form a surface coating layer by applying the resin component.

[0045] [Solvent solubility of resin components] From the viewpoint of facilitating the formation of a surface coating layer by application, the resin component is preferably soluble in organic solvents. Specifically, the resin component is preferably soluble in toluene at 23°C at a concentration of 1% by mass or more, more preferably soluble at a concentration of 5% by mass or more, and even more preferably soluble at a concentration of 8% by mass or more.

[0046] [Resin component content] The resin component content in the surface coating layer forming composition is preferably 50 to 99% by mass, more preferably 60 to 90% by mass, and even more preferably 70 to 85% by mass, based on the total amount (100% by mass) of the active ingredients of the surface coating layer forming composition. When the resin component content is above the lower limit mentioned above, the amount of grinding debris adhering tends to be reduced further. Conversely, when the resin component content is below the upper limit mentioned above, it tends to be easier to improve conveying performance by adding lubricity-enhancing components. In this embodiment, the active ingredients of the surface coating layer forming composition refer to the components contained in the surface coating layer forming composition, excluding components such as organic solvents that are removed during the process of forming the surface coating layer.

[0047] (Slippery properties improving component) The slipperiness-improving component contained in the surface coating layer-forming composition is an ingredient added to lower the static friction coefficient of the surface coating layer. Suitable components for improving lubricity include compounds with low surface free energy, such as resins having hydrocarbon groups in their side chains, and resins containing fluorine atoms in their main chain or side chains. Specifically, examples include silicone compounds and fluororesins, and among these, silicone compounds are preferred from the viewpoint of ease of handling.

[0048] [Silicone compounds] The silicone compound is not particularly limited as long as it is a polymer containing a polydiorganosiloxane structure. Examples of polydiorganosiloxane structures contained in silicone compounds include those having repeating units represented by the following general formula (1).

[0049] [ka] (In the formula, R is an independent hydrocarbon group having 1 to 6 carbon atoms. * represents a bonding site.)

[0050] The number of carbon atoms in the hydrocarbon group R, which has 1 to 6 carbon atoms, is preferably 1 to 4, more preferably 1 or 2, and even more preferably 1. Examples of C1-C6 hydrocarbon groups represented by R include C1-C5 alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, and n-pentyl groups; and phenyl groups. Among these, the methyl group is preferred.

[0051] The silicone compound may have a reactive functional group. When a silicone compound has a reactive functional group, it becomes possible to induce reactions between silicone compounds or between silicone compounds and other components, making it less likely for the silicone compound to bleed out from the surface coating layer. Examples of reactive functional groups include vinyl groups, (meth)acryloyl groups, and other functional groups containing ethylenically unsaturated bonds; glycidyl groups, amino groups, carboxyl groups, thiol groups, hydroxyl groups, etc. Among these, functional groups containing ethylenically unsaturated bonds are preferred, and (meth)acryloyl groups are more preferred. In this specification, "ethylenically unsaturated bond" means a carbon-carbon double bond capable of addition reactions, and does not include double bonds of aromatic rings. Furthermore, the (meth)acryloyl group may constitute a (meth)acryloyloxy group. When a silicone compound has a reactive functional group, the silicone compound may have the reactive functional group at the terminal or in the side chain, but it is preferable that it has the reactive functional group at the terminal. When a silicone compound has a reactive functional group at one end, the silicone compound may have the reactive functional group at one end or at both ends, but it is preferable that it has it at both ends. When the silicone compound has reactive functional groups, the equivalent amount of reactive functional groups in the silicone compound is not particularly limited, but is preferably 500 to 10,000 g / mol, more preferably 1,000 to 7,000 g / mol, and even more preferably 1,500 to 5,000 g / mol.

[0052] The silicone compound may be a linear polymer or a branched polymer, but a linear polymer is preferred. In other words, the silicone compound is preferably a linear polymer having reactive functional groups at both ends. Examples of such silicone compounds include those represented by the following general formula (2).

[0053] [ka] (In the formula, R is as described in the general formula (1) above. X is independently a divalent aliphatic hydrocarbon group having 1 to 5 carbon atoms, and Y is independently a reactive functional group.)

[0054] Preferred embodiments of R and preferred embodiments of the reactive functional group represented by Y are as described above. Examples of divalent aliphatic hydrocarbon groups with 1 to 5 carbon atoms represented by X include alkylene groups such as methanediyl group, ethane-1,2-diyl group, ethane-1,1-diyl group, n-propane-1,3-diyl group, n-propane-1,2-diyl group, 1,4-n-butyl group, 1,2-tert-butyl group, and 1,5-pentyl group.

[0055] The mass-average molecular weight (Mw) of the silicone compound is not particularly limited, but is preferably 1,000 to 20,000, more preferably 2,000 to 17,000, and even more preferably 3,000 to 15,000. When the mass-average molecular weight (Mw) of the silicone compound is above the lower limit, surface segregation of the silicone compound is suppressed, and the film-forming properties of the surface coating layer composition tend to be better, which in turn tends to improve transportability. Conversely, when the mass-average molecular weight (Mw) of the silicone compound is below the upper limit, the handling properties tend to be better.

[0056] The lubricity-enhancing component may or may not contain lubricity-enhancing components other than silicone compounds. The content of the silicone compound in the lubricity-improving component is preferably 90-100% by mass, more preferably 95-100% by mass, and even more preferably 98-100% by mass, from the viewpoint of further reducing the amount of abrasive debris adhering to the material and further improving its transportability.

[0057] [Heteroatom content of lubricity-enhancing components] The content of heteroatoms in the lubricity-improving component is not particularly limited, but is preferably 30% by mass or more, more preferably 40-80% by mass, and even more preferably 50-70% by mass.

[0058] [Content of lubricity-enhancing ingredients] The content of the slipperiness-improving component in the surface coating layer forming composition is preferably 0.1 to 30% by mass, more preferably 0.3 to 20% by mass, and even more preferably 0.5 to 10% by mass, based on the total amount (100% by mass) of the active ingredients of the surface coating layer forming composition. When the content of the lubricity-improving component is above the lower limit, the amount of grinding debris adhering to the material can be further reduced, and the transportability tends to improve. Conversely, when the content of the lubricity-improving component is below the upper limit, the adhesion between the buffer layer and the surface coating layer tends to improve.

[0059] (Energy-ray polymerizable polyfunctional compound) The surface coating layer forming composition preferably further contains an energy-ray polymerizable polyfunctional compound. The inclusion of an energy-ray polymerizable polyfunctional compound in the surface coating layer forming composition tends to result in the surface coating layer of the adhesive sheet of this embodiment exhibiting excellent adhesion to the buffer layer.

[0060] An energy-ray polymerizable polyfunctional compound is a compound having two or more energy-ray polymerizable functional groups. The number of energy-ray polymerizable functional groups in an energy-ray polymerizable polyfunctional compound is preferably 2 to 10, more preferably 3 to 8, and even more preferably 4 to 7. A (meth)acryloyl group is preferred as the energy-ray polymerizable functional group in an energy-ray polymerizable polyfunctional compound.

[0061] As the energy-ray polymerizable polyfunctional compound, polyfunctional (meth)acrylate monomers are preferred. Examples of polyfunctional (meth)acrylate monomers include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, neopentyl glycol adipate di(meth)acrylate, hydroxypivalate neopentyl glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified phosphate di(meth)acrylate, di(acryloxyethyl) isocyanurate, allylated cyclohexyl di(meth)acrylate, isocyanurate ethylene oxide-modified diacrylate, and other bifunctional (meth)acrylate monomers; trimethylolpropane tri(meth)acrylate, di Examples include pentaerythritol tri(meth)acrylate, propionic acid-modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate, tris(acryloxyethyl) isocyanurate, bis(acryloxyethyl)hydroxyethyl isocyanurate, ethylene oxide-modified isocyanurate triacrylate, ε-caprolactone-modified tris(acryloxyethyl) isocyanurate, diglycerin tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, propionic acid-modified dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate. Among these, dipentaerythritol hexa(meth)acrylate and dipentaerythritol penta(meth)acrylate are preferred, and dipentaerythritol hexaacrylate and dipentaerythritol pentaacrylate are more preferred.

[0062] The content of the energy-ray polymerizable polyfunctional compound in the surface coating layer forming composition is preferably 1 to 40% by mass, more preferably 5 to 30% by mass, and even more preferably 10 to 20% by mass, based on the total amount (100% by mass) of the active ingredients of the surface coating layer forming composition. When the content of the energy-ray polymerizable polyfunctional compound is above the lower limit, the surface coating layer tends to exhibit excellent adhesion to the buffer layer. Furthermore, when the content of the energy-ray polymerizable polyfunctional compound is below the upper limit, it tends to be easier to reduce the amount of grinding debris adhering to the surface and improve transportability by adding resin components and lubricity-enhancing components.

[0063] When the surface coating layer forming composition contains a resin component and an energy-ray polymerizable polyfunctional compound, the content of the energy-ray polymerizable polyfunctional compound is preferably 10 to 60 parts by mass, more preferably 14 to 40 parts by mass, and even more preferably 17 to 30 parts by mass, per 100 parts by mass of the resin component. When the content of the energy-ray polymerizable polyfunctional compound is above the lower limit, the surface coating layer tends to exhibit excellent adhesion to the buffer layer. Furthermore, when the content of the energy-ray polymerizable polyfunctional compound is below the upper limit, it tends to be easier to reduce the amount of grinding debris adhering to the surface and improve transportability by adding resin components and lubricity-enhancing components.

[0064] (Photopolymerization initiator) If the surface coating layer forming composition contains an energy-ray polymerizable polyfunctional compound, it is preferable that the surface coating layer forming composition further contains a photopolymerization initiator. The photopolymerization initiator may be used alone or in combination of two or more types.

[0065] Examples of photopolymerization initiators include benzoin compounds, acetophenone compounds, acyl phosphinoxide compounds, titanocene compounds, thioxanthone compounds, peroxide compounds, and photosensitizers such as amines and quinones. More specifically, examples include 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzyl phenyl sulfide, tetramethylthiuram monosulfide, azobisisobutyronitrile, dibenzyl, diacetyl, 8-chloroanthraquinone, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.

[0066] When a surface coating layer forming composition contains a photopolymerization initiator, the amount is not particularly limited, but from the viewpoint of ensuring that the energy ray polymerization reaction proceeds homogeneously and sufficiently, it is preferably 0.01 to 10 parts by mass, more preferably 0.03 to 7 parts by mass, and even more preferably 0.05 to 5 parts by mass, per 100 parts by mass of the energy ray polymerizable polyfunctional compound.

[0067] (Other ingredients) The surface coating layer may contain other components as long as they do not impair the effects of the present invention. Examples of other components include resins other than those mentioned above; additives such as antistatic agents, antioxidants, softeners, fillers, rust inhibitors, pigments, and dyes; and so on.

[0068] (contact angle) The static contact angle of water with respect to the surface coating layer of the adhesive sheet of this embodiment at 23°C (hereinafter also simply referred to as the "water contact angle") is preferably 85° or higher. When the water contact angle of the surface coating layer is 85° or higher, water containing grinding debris is less likely to adhere to the surface coating layer, which tends to further reduce the amount of grinding debris adhering to it. From the viewpoint of further reducing the amount of grinding debris adhering to the surface coating layer, the water contact angle is preferably 90° or higher, more preferably 95° or higher, and even more preferably 98° or higher. The upper limit of the water contact angle of the surface coating layer is not particularly limited, but from the viewpoint of ease of manufacturing, it may be, for example, 150° or lower, or 110° or lower. The water contact angle of the surface coating layer is a value measured in accordance with JIS R 3257:1999, and can be measured specifically by the method described in the examples.

[0069] The thickness of the surface coating layer is not particularly limited, but is preferably 0.05 to 10 μm, more preferably 0.2 to 7 μm, and even more preferably 1 to 4 μm. When the thickness of the surface coating layer is greater than or equal to the lower limit mentioned above, a uniform layer can be formed, which tends to further reduce the amount of grinding debris adhering to the surface and improve transportability. Conversely, when the thickness of the surface coating layer is less than or equal to the upper limit mentioned above, the buffering effect of absorbing irregularities such as foreign matter on the chuck table tends to be more easily achieved.

[0070] <Buffer layer> The buffer layer is a layer provided between the base material and the surface coating layer. It absorbs vibrations and shocks that occur during back grinding, preventing cracks from forming in the workpiece. Furthermore, by providing a buffer layer, it is possible to absorb irregularities such as foreign matter present on the table of the support device, thereby improving the support device's ability to hold the adhesive sheet.

[0071] (Buffer layer forming composition) The buffer layer can be formed from a buffer layer-forming composition. From the viewpoint of obtaining physical properties suitable for a buffer layer, it is preferable that the buffer layer is a layer obtained by energy ray curing of a buffer layer-forming composition containing an energy ray polymerizable compound. The buffer layer forming composition preferably contains urethane (meth)acrylate (a1) as an energy-ray polymerizable compound. The inclusion of urethane (meth)acrylate (a1) in the buffer layer forming composition tends to allow the storage modulus of the buffer layer to be adjusted to a favorable range. Furthermore, from a similar viewpoint, the buffer layer forming composition more preferably contains, in addition to urethane (meth)acrylate (a1), one or more polymerizable compounds selected from the group consisting of polymerizable compounds having alicyclic or heterocyclic groups with 6 to 20 ring-forming atoms (a2) and polymerizable compounds having functional groups (a3). It is even more preferable that, in addition to urethane (meth)acrylate (a1), it contains polymerizable compounds having alicyclic or heterocyclic groups with 6 to 20 ring-forming atoms (a2) and polymerizable compounds having functional groups (a3). In this specification, the number of ring-forming atoms refers to the number of atoms that constitute the ring itself in a compound with a structure in which atoms are bonded in a ring. Atoms that do not constitute a ring (for example, hydrogen atoms bonded to atoms that constitute a ring), and atoms included in substituents when the ring is substituted by substituents, are not included in the number of ring-forming atoms.

[0072] [Urethane (meth)acrylate (a1)] Urethane (meth)acrylate (a1) is a compound having a (meth)acryloyl group and a urethane bond, and has the property of polymerizing upon irradiation with energy rays. Urethane (meth)acrylate (a1) may be used alone or in combination of two or more types.

[0073] The mass-average molecular weight (Mw) of urethane (meth)acrylate (a1) is not particularly limited, but is preferably 1,000 to 100,000, more preferably 2,000 to 60,000, and even more preferably 3,000 to 20,000. In this embodiment, the mass-average molecular weight (Mw) refers to the value on a standard polystyrene basis measured by gel permeation chromatography (GPC), and specifically, the value measured by the method described in the example.

[0074] The number of (meth)acryloyl groups in one molecule of urethane (meth)acrylate (a1) is not particularly limited, but is preferably 1 to 4, more preferably 1 to 3, and even more preferably 1 or 2.

[0075] Urethane (meth)acrylate (a1) can be obtained, for example, by reacting a terminal isocyanate urethane prepolymer, which is obtained by reacting a polyol compound with a polyvalent isocyanate compound, with a (meth)acrylate having a hydroxyl group.

[0076] The polyol compound is not particularly limited as long as it is a compound having two or more hydroxyl groups. Specific examples of polyol compounds include alkylenediols, polyether-type polyols, polyester-type polyols, and polycarbonate-type polyols. Among these, polyester-type polyols are preferred. The polyol compound may be a bifunctional diol, a trifunctional triol, or a polyol with four or more functions, but a bifunctional diol is preferred, and a polyester-type diol is more preferred. Polyol compounds may be used individually or in combination of two or more.

[0077] Examples of polyvalent isocyanate compounds include aliphatic polyisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate, and trimethylhexamethylene diisocyanate; alicyclic diisocyanates such as isophorone diisocyanate, norbornane diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, dicyclohexylmethane-2,4'-diisocyanate, and ω,ω'-diisocyanate dimethylcyclohexane; and aromatic diisocyanates such as 4,4'-diphenylmethane diisocyanate, tolylene diisocyanate, xylylene diisocyanate, tolidine diisocyanate, tetramethylene xylylene diisocyanate, and naphthalene-1,5-diisocyanate. Among these, isophorone diisocyanate, hexamethylene diisocyanate, and xylylene diisocyanate are preferred. Polyvalent isocyanate compounds may be used individually or in combination of two or more.

[0078] The (meth)acrylate having a hydroxyl group to be reacted with the terminal isocyanate urethane prepolymer is not particularly limited, as long as it is a compound having at least one molecule containing both a hydroxyl group and a (meth)acryloyl group. Examples of (meth)acrylates having a hydroxyl group include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 4-hydroxycyclohexyl (meth)acrylate, 5-hydroxycyclooctyl (meth)acrylate, 2-hydroxy-3-phenyloxypropyl (meth)acrylate, pentaerythritol tri(meth)acrylate, polyethylene glycol mono(meth)acrylate, and polypropylene glycol mono(meth)acrylate; hydroxyl group-containing (meth)acrylamides such as N-methylol (meth)acrylamide; and reaction products obtained by reacting vinyl alcohol, vinyl phenol, or diglycidyl ester of bisphenol A with (meth)acrylic acid. Among these, hydroxyalkyl (meth)acrylates are preferred, and 2-hydroxyethyl (meth)acrylate is more preferred. The (meth)acrylates having a hydroxyl group may be used individually or in combination of two or more.

[0079] The conditions for reacting the terminal isocyanate urethane prepolymer with the (meth)acrylate having a hydroxyl group are not particularly limited, but for example, the reaction can be carried out at 60-100°C for 1-4 hours in the presence of an organic solvent, catalyst, etc., which may be added as needed.

[0080] The content of urethane (meth)acrylate (a1) in the buffer layer forming composition is not particularly limited, but is preferably 10 to 70% by mass, more preferably 20 to 60% by mass, and even more preferably 30 to 50% by mass, based on the total amount (100% by mass) of the active ingredients of the buffer layer forming composition. In this embodiment, the active ingredients of the buffer layer forming composition refer to the components contained in the buffer layer forming composition, excluding components such as organic solvents that are removed during the process of forming the buffer layer.

[0081] [Polymerizable compounds having alicyclic or heterocyclic groups with 6 to 20 ring-forming atoms (a2)] The film-forming properties of a buffer layer-forming composition tend to improve when it contains a polymerizable compound (a2) having an alicyclic or heterocyclic group with 6 to 20 ring-forming atoms (hereinafter also referred to as "polymerizable compound (a2) having an alicyclic or heterocyclic group"). Examples of atoms that form the ring structure of a heterocyclic group include carbon atoms, nitrogen atoms, oxygen atoms, and sulfur atoms. Polymerizable compounds (a2) having an alicyclic group or a heterocyclic group may be used individually or in combination of two or more.

[0082] The polymerizable compound (a2) having an alicyclic or heterocyclic group is preferably a compound having a (meth)acryloyl group. The number of (meth)acryloyl groups in one molecule of a polymerizable compound (a2) having an alicyclic or heterocyclic group is not particularly limited, but is preferably one or more, more preferably one or two, and even more preferably one.

[0083] The polymerizable compound (a2) having an alicyclic or heterocyclic group has 6 to 20 ring-forming atoms in the alicyclic or heterocyclic group, preferably 6 to 18, more preferably 6 to 16, and even more preferably 7 to 12.

[0084] Examples of polymerizable compounds (a2) having an alicyclic or heterocyclic group include alicyclic group-containing (meth)acrylates such as isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxy (meth)acrylate, cyclohexyl (meth)acrylate, and adamantane (meth)acrylate; and heterocyclic group-containing (meth)acrylates such as tetrahydrofurfuryl (meth)acrylate and morpholine (meth)acrylate. Among these, alicyclic group-containing (meth)acrylates are preferred, and isobornyl (meth)acrylate is more preferred.

[0085] The content of polymerizable compounds (a2) having alicyclic or heterocyclic groups in the buffer layer forming composition is not particularly limited, but is preferably 10 to 70% by mass, more preferably 20 to 60% by mass, and even more preferably 30 to 50% by mass, based on the total amount (100% by mass) of the active ingredients of the buffer layer forming composition.

[0086] [Polymerizable compounds having functional groups (a3)] The presence of a polymerizable compound (a3) ​​having a functional group in the buffer layer-forming composition tends to allow the viscosity of the buffer layer-forming composition to be adjusted to an appropriate range. Polymerizable compounds (a3) ​​having functional groups may be used individually or in combination of two or more.

[0087] Examples of functional groups found in polymerizable compounds (a3) ​​include hydroxyl groups, epoxy groups, amide groups, and amino groups. The number of functional groups in one molecule of the polymerizable compound (a3) ​​having a functional group is one or more, preferably 1 to 3, more preferably 1 or 2, and even more preferably 1.

[0088] The polymerizable compound (a3) ​​having a functional group is preferably a compound having a (meth)acryloyl group together with the functional group. The number of (meth)acryloyl groups in one molecule of the polymerizable compound (a3) ​​having a functional group is not particularly limited, but is preferably one or more, more preferably one or two, and even more preferably one.

[0089] Examples of polymerizable compounds having functional groups (a3) ​​include hydroxyl group-containing polymerizable compounds, epoxy group-containing polymerizable compounds, amide group-containing polymerizable compounds, amino group-containing polymerizable compounds, and the like.

[0090] Examples of hydroxyl group-containing polymerizable compounds include hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate; vinyl ether compounds such as hydroxyethyl vinyl ether and hydroxybutyl vinyl ether; and the like.

[0091] Examples of epoxy group-containing polymerizable compounds include glycidyl (meth)acrylate, methylglycidyl (meth)acrylate, and allyl glycidyl ether.

[0092] Examples of polymerizable compounds containing amide groups include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylolpropane(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, and N-vinylformamide.

[0093] Examples of amino group-containing polymerizable compounds include amino group-containing (meth)acrylates such as primary amino group-containing (meth)acrylates, secondary amino group-containing (meth)acrylates, and tertiary amino group-containing (meth)acrylates.

[0094] Among these, hydroxyl group-containing (meth)acrylates are preferred, and hydroxyl group-containing (meth)acrylates having an aromatic ring, such as 2-hydroxy-3-phenoxypropyl (meth)acrylate, are more preferred.

[0095] The content of the polymerizable compound (a3) ​​having a functional group in the buffer layer forming composition is not particularly limited, but is preferably 5 to 40% by mass, more preferably 10 to 30% by mass, and even more preferably 15 to 25% by mass, based on the total amount (100% by mass) of the active ingredients of the buffer layer forming composition.

[0096] [Other polymerizable compounds] The buffer layer forming composition may contain other polymerizable compounds other than components (a1) to (a3), as long as the effects of the present invention are not impaired. Other polymerizable compounds include, for example, alkyl (meth)acrylates having alkyl groups with 1 to 20 carbon atoms; vinyl compounds such as styrene, N-vinylpyrrolidone, and N-vinylcaprolactam; and so on. Other polymerizable compounds may be used individually or in combination of two or more. The content of other polymerizable compounds in the buffer layer forming composition is not particularly limited, but is preferably 0 to 20% by mass, more preferably 0 to 10% by mass, and even more preferably 0 to 2% by mass, based on the total amount (100% by mass) of the active ingredients of the buffer layer forming composition.

[0097] [Photopolymerization initiator] A buffer layer-forming composition containing an energy-ray polymerizable compound is preferably further containing a photopolymerization initiator, from the viewpoint of reducing the polymerization time and energy-ray irradiation dose. The photopolymerization initiator may be used alone or in combination of two or more types.

[0098] Examples of photopolymerization initiators include benzoin compounds, acetophenone compounds, acyl phosphinoxide compounds, titanocene compounds, thioxanthone compounds, peroxide compounds, and photosensitizers such as amines and quinones. More specifically, examples include 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzyl phenyl sulfide, tetramethylthiuram monosulfide, azobisisobutyronitrile, dibenzyl, diacetyl, 8-chloroanthraquinone, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide. Among these, 1-hydroxycyclohexyl phenyl ketone is preferred.

[0099] The amount of photopolymerization initiator in the buffer layer forming composition is not particularly limited, but from the viewpoint of ensuring that the energy ray curing reaction proceeds homogeneously and sufficiently, it is preferably 0.05 to 15 parts by mass, more preferably 0.1 to 10 parts by mass, and even more preferably 0.3 to 5 parts by mass, per 100 parts by mass of the total amount of energy ray polymerizable compounds.

[0100] (Other ingredients) The buffer layer forming composition may contain other components as long as they do not impair the effects of the present invention. Examples of other components include resin components other than the resins described above; and other additives such as antistatic agents, antioxidants, softeners, fillers, rust inhibitors, pigments, and dyes. The content of other resin components in the buffer layer forming composition is not particularly limited, but is preferably 0 to 20% by mass, more preferably 0 to 10% by mass, and even more preferably 0 to 2% by mass, relative to the total amount (100% by mass) of the active ingredients of the buffer layer forming composition. The content of other additives in the buffer layer forming composition is not particularly limited, but each is preferably 0 to 6% by mass, more preferably 0.01 to 5% by mass, and even more preferably 0.1 to 3% by mass, relative to the total amount (100% by mass) of the active ingredients of the buffer layer forming composition.

[0101] (Young's modulus of the buffer layer) The Young's modulus of the buffer layer at 23°C is smaller than that of the substrate at 23°C, specifically, preferably less than 1,200 MPa, more preferably 900 MPa or less. Furthermore, the Young's modulus of the buffer layer at 23°C is preferably 50 MPa or more, more preferably 100 MPa or more. When the Young's modulus of the buffer layer at 23°C is below the upper limit, the effect of absorbing vibrations and shocks generated during back grinding and the retention of the adhesive sheet tend to improve. Conversely, when the Young's modulus of the buffer layer at 23°C is above the lower limit, excessive deformation of the buffer layer during workpiece processing tends to be suppressed. The Young's modulus of the buffer layer at 23°C can be measured in accordance with JIS K 7127:1999 under conditions of a test speed of 200 mm / min.

[0102] (Stress relaxation rate of the buffer layer) The stress relaxation rate of the buffer layer is not particularly limited, but is preferably 70-100%, more preferably 75-100%, and even more preferably 78-98%. When the stress relaxation rate of the buffer layer is within the above range, the effect of absorbing vibrations and shocks generated during backside grinding and the retention of the adhesive sheet tend to be higher. The stress relaxation rate of the buffer layer is determined by using a 200 μm thick buffer layer cut into a 15 mm x 140 mm specimen, gripping both ends of the specimen at 20 mm / min, and stretching it by 10% at a rate of 200 mm / min. The stress A (N / m) is measured in this specimen. 2 ), and stress B (N / m) 1 minute after extension cessation. 2 Using the value of ), it can be calculated from the following formula. Stress relaxation rate (%) = 100 × (AB) / A (%)

[0103] (Thickness of the buffer layer) The thickness of the buffer layer is not particularly limited, but is preferably 5 to 70 μm, more preferably 7 to 50 μm, and even more preferably 10 to 40 μm. When the thickness of the buffer layer is greater than or equal to the lower limit mentioned above, the effect of absorbing vibrations and shocks generated during back grinding and the retention of the adhesive sheet tend to be higher. Conversely, when the thickness of the buffer layer is less than or equal to the upper limit mentioned above, the excessive deformation of the buffer layer during workpiece processing tends to be suppressed.

[0104] <Adhesive layer> The adhesive layer is a layer provided on the side of the substrate opposite to the buffer layer, and is the layer that is attached to the workpiece. The adhesive layer is preferably formed from an energy-ray curable adhesive. By forming the adhesive layer from an energy-ray curable adhesive, the workpiece surface can be well protected by sufficient tackiness before energy-ray curing, and the peeling force is reduced after energy-ray curing, making it easy to peel off from the workpiece.

[0105] Examples of energy-ray curable adhesives include the following X-type adhesive composition, Y-type adhesive composition, XY-type adhesive composition, etc. Type X adhesive composition: An energy-ray curable adhesive composition containing a non-energy-ray curable adhesive resin (hereinafter also referred to as "adhesive resin I") and an energy-ray curable compound other than the adhesive resin. Y-type adhesive composition: An energy-ray curable adhesive composition containing an energy-ray curable adhesive resin (hereinafter also referred to as "adhesive resin II") in which an unsaturated group is introduced into the side chain of a non-energy-ray curable adhesive resin, and which does not contain any energy-ray curable compounds other than the adhesive resin. XY-type adhesive composition: An energy-ray curable adhesive composition containing the above-mentioned energy-ray curable adhesive resin II and an energy-ray curable compound other than the adhesive resin. Among these, energy-ray curable adhesives are preferably XY-type adhesive compositions. By using an XY-type adhesive composition, it is possible to have sufficient tackiness before curing while significantly reducing the peeling force from the workpiece after curing.

[0106] The adhesive forming the adhesive layer may be a layer formed from a non-energy-ray-curable adhesive that does not harden when irradiated with energy rays. Examples of non-energy ray curable adhesives include those containing adhesive resin I but not adhesive resin II or energy ray curable compounds.

[0107] Next, we will explain in more detail each component that makes up the adhesive layer. In the following description, "adhesive resin" is used as a term referring to either or both of adhesive resin I and adhesive resin II. Furthermore, in the following description, when simply referred to as "adhesive composition," the concept includes X-type adhesive composition, Y-type adhesive composition, XY-type adhesive composition, and other adhesive compositions.

[0108] Examples of adhesive resins include acrylic resins, urethane resins, rubber resins, and silicone resins. Among these, acrylic resins are preferred.

[0109] (Acrylic resin) The acrylic resin preferably contains constituent units derived from alkyl (meth)acrylate. Examples of alkyl (meth)acrylates include alkyl (meth)acrylates in which the alkyl group has 1 to 20 carbon atoms. The alkyl group in the alkyl (meth)acrylate may be linear or branched.

[0110] From the viewpoint of further improving the adhesive strength of the adhesive layer, it is preferable that the acrylic resin contains constituent units derived from alkyl (meth)acrylates in which the alkyl group has 4 or more carbon atoms. The constituent units derived from alkyl (meth)acrylates containing alkyl groups with 4 or more carbon atoms in the acrylic resin may be one type alone or two or more types. The alkyl(meth)acrylate having four or more carbon atoms in the alkyl group preferably has 4 to 12 carbon atoms, more preferably 4 to 8 carbon atoms, and even more preferably 4 to 6 carbon atoms. Examples of alkyl (meth)acrylates having four or more carbon atoms in the alkyl group include butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate. Among these, butyl (meth)acrylate is preferred, and butyl acrylate is more preferred. When the acrylic resin contains constituent units derived from alkyl (meth)acrylate having four or more carbon atoms in the alkyl group, the content thereof is preferably 30 to 90% by mass, more preferably 40 to 80% by mass, and even more preferably 45 to 60% by mass, in the acrylic resin, from the viewpoint of further improving the adhesive strength of the adhesive layer.

[0111] From the viewpoint of improving the storage modulus G' and adhesive properties of the adhesive layer, it is preferable that the acrylic resin contains both structural units derived from alkyl (meth)acrylates having 4 or more carbon atoms in the alkyl group, and structural units derived from alkyl (meth)acrylates having 1 to 3 carbon atoms in the alkyl group. The constituent units derived from alkyl (meth)acrylates containing alkyl groups with 1 to 3 carbon atoms in the acrylic resin may be one type alone or two or more types. Examples of alkyl(meth)acrylates having 1 to 3 carbon atoms in the alkyl group include methyl(meth)acrylate, ethyl(meth)acrylate, isopropyl(meth)acrylate, and n-propyl(meth)acrylate. Among these, methyl(meth)acrylate and ethyl(meth)acrylate are preferred, methyl(meth)acrylate is more preferred, and methyl methacrylate is even more preferred. When the acrylic resin contains constituent units derived from alkyl (meth)acrylates having 1 to 3 carbon atoms in the alkyl group, the content of these units is preferably 1 to 35% by mass, more preferably 5 to 30% by mass, and even more preferably 15 to 25% by mass, in the acrylic resin.

[0112] The acrylic resin preferably further contains constituent units derived from functional group-containing monomers. By containing structural units derived from functional group-containing monomers in acrylic resins, it is possible to introduce functional groups that act as crosslinking starting points that react with crosslinking agents, or functional groups that react with unsaturated group-containing compounds to introduce unsaturated groups into the side chains of the acrylic resin. The constituent units derived from functional group-containing monomers contained in the acrylic resin may be one type alone or two or more types.

[0113] Examples of functional group-containing monomers include hydroxyl group-containing monomers, carboxyl group-containing monomers, amino group-containing monomers, and epoxy group-containing monomers. Among these, hydroxyl group-containing monomers and carboxyl group-containing monomers are preferred, and hydroxyl group-containing monomers are more preferred. Examples of hydroxyl group-containing monomers include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; unsaturated alcohols such as vinyl alcohol and allyl alcohol; and the like. Examples of monomers containing a carboxyl group include ethylenically unsaturated monocarboxylic acids such as (meth)acrylic acid and crotonic acid; ethylenically unsaturated dicarboxylic acids such as fumaric acid, itaconic acid, maleic acid, and citraconic acid, and their anhydrides; and 2-carboxyethyl methacrylate.

[0114] When an acrylic resin contains constituent units derived from functional group-containing monomers, the content is not particularly limited, but is preferably 5 to 45% by mass, more preferably 15 to 40% by mass, and even more preferably 25 to 35% by mass in the acrylic resin.

[0115] In addition to the above-mentioned structural units, the acrylic resin may also contain structural units derived from other monomers copolymerizable with acrylic monomers. The constituent units derived from other monomers contained in the acrylic resin may be one type alone or two or more types. Other monomers include, for example, styrene, α-methylstyrene, vinyltoluene, vinyl formate, vinyl acetate, acrylonitrile, and acrylamide.

[0116] The acrylic resin may also be modified by introducing unsaturated groups that are capable of energy ray polymerization in order to impart energy ray curability. Unsaturated groups can be introduced, for example, by reacting a functional group of an acrylic resin containing a structural unit derived from a functional group-containing monomer with a reactive substituent of a compound having a reactive substituent and an unsaturated group that are reactive with the functional group (hereinafter also referred to as an "unsaturated group-containing compound"). The unsaturated group-containing compound may be used alone or in combination of two or more types. Examples of unsaturated groups found in compounds containing unsaturated groups include (meth)acryloyl groups, vinyl groups, and allyl groups. Among these, (meth)acryloyl groups are preferred. Examples of reactive substituents found in unsaturated group-containing compounds include isocyanate groups and glycidyl groups. Examples of compounds containing unsaturated groups include (meth)acryloyloxyethyl isocyanate, (meth)acryloyl isocyanate, and glycidyl (meth)acrylate.

[0117] When an acrylic resin containing structural units derived from functional group-containing monomers is reacted with an unsaturated group-containing compound, the ratio of functional groups that react with the unsaturated group-containing compound to the total number of functional groups in the acrylic resin is not particularly limited, but is preferably 60 to 98 mol%, more preferably 70 to 95 mol%, and even more preferably 80 to 93 mol%. When the ratio of functional groups that react with the unsaturated group-containing compound is within the above range, sufficient energy ray curability can be imparted to the acrylic resin, and the functional groups that did not react with the unsaturated group-containing compound can be reacted with the crosslinking agent to crosslink the acrylic resin.

[0118] The mass-average molecular weight (Mw) of the acrylic resin is not particularly limited, but is preferably 300,000 to 1,500,000, more preferably 350,000 to 1,000,000, and even more preferably 400,000 to 600,000. When the mass-average molecular weight (Mw) of the acrylic resin is within the above range, the adhesive strength and cohesive strength of the adhesive layer tend to be better.

[0119] (Energy ray curable compound) As the energy-ray curable compound contained in the X-type or XY-type adhesive composition, monomers or oligomers having an unsaturated group in the molecule and capable of being cured by energy-ray irradiation are preferred. Examples of energy-ray curable compounds include polyvalent (meth)acrylate monomers such as trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate; and oligomers such as urethane(meth)acrylate, polyester(meth)acrylate, polyether(meth)acrylate, and epoxy(meth)acrylate. Among these, urethane(meth)acrylate oligomers are preferred from the viewpoint of having a relatively high molecular weight and not easily reducing the elastic modulus of the adhesive layer.

[0120] The molecular weight of the energy-ray-curable compound is not particularly limited, but is preferably 100 to 12,000, more preferably 200 to 10,000, even more preferably 400 to 8,000, and even more preferably 600 to 6,000. When the energy-ray-curable compound is an oligomer, the above molecular weight refers to the mass-average molecular weight (Mw).

[0121] The content of the energy ray curable compound in the X-type adhesive composition is not particularly limited, but is preferably 40 to 200 parts by mass, more preferably 50 to 150 parts by mass, and even more preferably 60 to 90 parts by mass, per 100 parts by mass of adhesive resin. When the content of the energy-curable compound in the X-type adhesive composition is within the above range, there is a tendency for a good balance between the adhesive strength before energy irradiation and the peelability after energy irradiation.

[0122] The content of the energy ray curable compound in the XY-type adhesive composition is not particularly limited, but is preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, and even more preferably 3 to 15 parts by mass, per 100 parts by mass of adhesive resin. When the content of the energy-ray-curable compound in the XY-type adhesive composition is within the above range, a good balance between the adhesive strength before energy irradiation and the peelability after energy irradiation tends to be achieved. Furthermore, because the adhesive resin in the XY-type adhesive composition is energy-ray-curable, even with a low content of the energy-ray-curable compound, the peelability after energy irradiation tends to be sufficiently reduced.

[0123] (Crosslinking agent) The adhesive composition preferably further contains a crosslinking agent. A crosslinking agent, for example, crosslinks adhesive resins by reacting with functional groups derived from functional group-containing monomers present in the adhesive resin. The crosslinking agent may be used alone or in combination of two or more types.

[0124] Examples of crosslinking agents include isocyanate-based crosslinking agents such as tolylene diisocyanate, hexamethylene diisocyanate, and their adducts; epoxy-based crosslinking agents such as ethylene glycol glycidyl ether; aziridine-based crosslinking agents such as hexa[1-(2-methyl)-aziridinyl]triphosphatriadin; and chelate-based crosslinking agents such as aluminum chelate. Among these, isocyanate-based crosslinking agents are preferred from the viewpoint of increasing cohesive force and improving adhesion, as well as from the viewpoint of availability.

[0125] When the adhesive composition contains a crosslinking agent, the amount is not particularly limited, but from the viewpoint of allowing the crosslinking reaction to proceed appropriately, it is preferably 0.01 to 10 parts by mass, more preferably 0.03 to 7 parts by mass, and even more preferably 0.05 to 4 parts by mass per 100 parts by mass of adhesive resin.

[0126] (Photopolymerization initiator) When the adhesive is an energy-ray curable adhesive, it is preferable that the adhesive composition further contains a photopolymerization initiator. The presence of a photopolymerization initiator in an energy-ray curable adhesive tends to allow the curing reaction to proceed sufficiently even with relatively low-energy energy rays such as ultraviolet light. The photopolymerization initiator may be used alone or in combination of two or more types.

[0127] Examples of photopolymerization initiators include benzoin compounds, acetophenone compounds, acyl phosphinoxide compounds, titanocene compounds, thioxanthone compounds, peroxide compounds, and photosensitizers such as amines and quinones. More specifically, examples include 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzyl phenyl sulfide, tetramethylthiuram monosulfide, azobisisobutyronitrile, dibenzyl, diacetyl, 8-chloroanthraquinone, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.

[0128] When an energy-ray curable adhesive contains a photopolymerization initiator, the amount is not particularly limited, but from the viewpoint of ensuring that the energy-ray curing reaction proceeds homogeneously and sufficiently, it is preferably 0.01 to 10 parts by mass, more preferably 0.03 to 7 parts by mass, and even more preferably 0.05 to 5 parts by mass per 100 parts by mass of adhesive resin.

[0129] (Other additives) The adhesive composition may contain other additives as long as they do not impair the effects of the present invention. Examples of other additives include antistatic agents, antioxidants, softeners, fillers, rust inhibitors, pigments, dyes, and the like. The content of other additives in the adhesive composition is not particularly limited, but each is preferably 0 to 6% by mass, more preferably 0.01 to 5% by mass, and even more preferably 0.1 to 3% by mass, relative to the total amount (100% by mass) of the active ingredients of the adhesive composition. In this embodiment, the active ingredient of the adhesive composition refers to the components contained in the adhesive composition, excluding components such as organic solvents that are removed during the process of forming the adhesive layer.

[0130] (organic solvent) The adhesive composition may be diluted with an organic solvent to form a solution, from the viewpoint of further improving its applicability to substrates, release sheets, etc. Examples of organic solvents include methyl ethyl ketone, acetone, ethyl acetate, tetrahydrofuran, dioxane, cyclohexane, n-hexane, toluene, xylene, n-propanol, and isopropanol. Organic solvents may be used individually or in combination of two or more. The organic solvent may be the same organic solvent used during the synthesis of the adhesive resin, or one or more organic solvents other than those used during the synthesis may be added.

[0131] The storage modulus G' of the adhesive layer at 23°C is not particularly limited, but is preferably 0.05 to 0.5 MPa, more preferably 0.1 to 0.4 MPa, and even more preferably 0.12 to 0.3 MPa. When the storage modulus G' of the adhesive layer at 23°C is within the above range, an adhesive layer with excellent conformability to uneven surfaces can be obtained, even when the workpiece surface is uneven, and the workpiece surface tends to be better protected during processing. Furthermore, if the adhesive layer is formed from an energy-ray curable adhesive, the storage modulus G' of the adhesive layer refers to the storage modulus G' before curing by energy-ray irradiation. The storage modulus G' of the adhesive layer at 23°C can be measured using a viscoelasticity measuring device with a torsional shear method, using a 3mm thick adhesive layer cut into a circular shape with a diameter of 8mm as the test specimen, under the conditions of a frequency of 1Hz and a measurement temperature of 23°C.

[0132] The thickness of the adhesive layer is not particularly limited, but is preferably 5 to 100 μm, more preferably 10 to 80 μm, and even more preferably 15 to 60 μm. When the thickness of the adhesive layer is greater than or equal to the lower limit mentioned above, excellent adhesion is obtained, and the surface of the workpiece tends to be better protected during processing. Conversely, when the thickness of the adhesive layer is less than or equal to the upper limit mentioned above, the generation of tape scraps when cutting the adhesive sheet is suppressed, and damage to the workpiece tends to be better prevented.

[0133] <Base material> Examples of substrates include various resin films. Examples of resins constituting the resin films include polyethylene such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE); polyolefins such as polypropylene, polybutene, polybutadiene, polymethylpentene, ethylene-norbornene copolymer, and norbornene resin; ethylene copolymers such as ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid copolymer, and ethylene-(meth)acrylic acid ester copolymer; polyvinyl chloride such as polyvinyl chloride and vinyl chloride copolymer; polyesters such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, and fully aromatic polyester; polyurethane, polyimide, polyamide, polycarbonate, fluororesin, polyacetal, modified polyphenylene oxide, polyphenylene sulfide, polysulfone, polyether ketone, and acrylic polymers. The substrate may be a single-layer resin film made of one or more resins selected from these resins, or a laminated film made by laminating two or more of these resin films. Alternatively, it may be a modified film such as a crosslinked film or ionomer film of the above resins. Among these resin films, the base material is preferably one or more selected from polyester film, polyamide film, polyimide film, and biaxially oriented polypropylene film, with polyester film being more preferred and polyethylene terephthalate film being even more preferred.

[0134] The Young's modulus of the substrate is not particularly limited, but is preferably 1,000 MPa or more, more preferably 1,800 to 30,000 MPa, and even more preferably 2,500 to 6,000 MPa. When the Young's modulus of the base material is above the lower limit, the vibration suppression effect during workpiece processing tends to improve. Conversely, when the Young's modulus of the base material is below the upper limit, the workability when attaching it to the workpiece and when peeling it off the workpiece tends to improve. The Young's modulus of the substrate can be measured in accordance with JIS K 7127:1999 under conditions of a test speed of 200 mm / min.

[0135] The thickness of the substrate is not particularly limited, but is preferably 10 to 200 μm, more preferably 25 to 100 μm, and even more preferably 30 to 70 μm. When the thickness of the base material is greater than or equal to the lower limit mentioned above, sufficient strength for functioning as a support for the adhesive sheet tends to be obtained. Conversely, when the thickness of the base material is less than or equal to the upper limit mentioned above, moderate flexibility is obtained, and handling tends to improve. Note that "base material thickness" refers to the total thickness of the base material. If the base material consists of multiple layers, it refers to the total thickness of all the layers that make up the base material.

[0136] The base material may contain plasticizers, lubricants, infrared absorbers, ultraviolet absorbers, fillers, colorants, antistatic agents, antioxidants, catalysts, etc., to the extent that it does not impair the effects of the present invention. The substrate may be transparent or opaque, and may be colored or vapor-deposited as desired. The substrate may have surface treatment, such as corona treatment, applied to at least one surface, from the viewpoint of improving adhesion with other layers, or it may have a coating layer provided for the purpose of improving adhesion.

[0137] <Release sheet> The adhesive sheet of this embodiment may have a release sheet attached to at least one of the surfaces of the adhesive layer and the surface of the surface coating layer. The release sheet protects the surface of the adhesive sheet by being peelably attached to the surface of the adhesive sheet before use, and is peeled off and removed when the adhesive sheet is used. The release sheet may be a release sheet that has been treated to peel on one side, or a release sheet that has been treated to peel on both sides. As for the release sheet, a release sheet in which a release agent is applied to a release sheet substrate is preferred. A resin film is preferred as the substrate for the release sheet, and examples of such resin films include polyester films such as polyethylene terephthalate film, polybutylene terephthalate film, and polyethylene naphthalate film; polyolefin films such as polypropylene film and polyethylene film; and the like. Examples of release agents include rubber elastomers such as silicone resins, olefin resins, isoprene resins, and butadiene resins; and long-chain alkyl resins, alkyd resins, and fluororesins. The thickness of the release sheet is not particularly limited, but is preferably 5 to 200 μm, more preferably 10 to 100 μm, and even more preferably 20 to 50 μm.

[0138] The total thickness of the adhesive sheet in this embodiment is not particularly limited, but is preferably 30 to 300 μm, more preferably 40 to 220 μm, and even more preferably 45 to 160 μm. When the total thickness of the adhesive sheet is above the lower limit, the adhesive performance of the adhesive layer and the shock absorption performance of the buffer layer are appropriately maintained, and the adhesive sheet tends to fully perform its function as an adhesive sheet for semiconductor processing. Conversely, when the total thickness of the adhesive sheet is below the upper limit, the peeling force required when peeling the workpiece from the adhesive sheet tends to be reduced. In this embodiment, "total thickness of the adhesive sheet" refers to the thickness from the surface of the surface coating layer to the surface of the adhesive layer of the adhesive sheet, and if a release sheet is provided, the thickness of the release sheet is not included in the total thickness.

[0139] <Method for manufacturing adhesive sheets> There are no particular limitations on the method for manufacturing the adhesive sheet of this embodiment, and it can be manufactured by known methods. The adhesive sheet of this embodiment can be manufactured, for example, by a method comprising the steps of forming an adhesive layer on one side of a substrate (hereinafter also referred to as the "adhesive layer formation step"), forming a buffer layer on the other side of the substrate (hereinafter also referred to as the "buffer layer formation step"), and forming a surface coating layer on the side of the buffer layer opposite to the substrate (hereinafter also referred to as the "surface coating layer formation step"). The order of these steps is not particularly limited, and they may be performed simultaneously if they can be performed at the same time.

[0140] Methods for forming an adhesive layer, a buffer layer, or a surface coating layer include, for example, applying an adhesive composition, a buffer layer forming composition, or a coating liquid for a surface coating layer to a predetermined position by a known method, and then, if necessary, performing energy ray irradiation, heat drying, or the like.

[0141] Methods for applying adhesive compositions, buffer layer forming compositions, or coating liquids for surface coating layers include, for example, spin coating, spray coating, bar coating, knife coating, roll coating, blade coating, die coating, and gravure coating.

[0142] The adhesive layer formation step may be, for example, a method of bonding an adhesive layer formed on a release sheet to the surface of a substrate, or a method of forming an adhesive layer by directly applying an adhesive composition to the surface of a substrate. In the buffer layer formation process, the buffer layer forming composition may be applied to a release sheet or applied directly to the surface of the substrate. When the buffer layer forming composition is applied to a release sheet, the layer formed from the buffer layer forming composition on the release sheet (hereinafter also referred to as the "buffer layer forming composition layer") is then attached to the surface of the substrate. The buffer layer forming composition layer on the release sheet may be the buffer layer itself, or, if the buffer layer forming composition is curable, it may be an uncured or semi-cured product of the curable buffer layer forming composition. When an uncured or semi-cured product of the buffer layer forming composition is formed on the substrate, the buffer layer forming composition is then subjected to a process to fully cure it. In the surface coating layer formation process, the coating liquid for the surface coating layer may be applied to a release sheet or directly to the surface of the buffer layer. When the coating liquid for the surface coating layer is applied to a release sheet, the layer formed from the surface coating layer forming composition on the release sheet (hereinafter also referred to as the "surface coating layer forming composition layer") is then attached to the surface of the buffer layer. The surface coating layer forming composition layer on the release sheet may be the surface coating layer itself, or, if the surface coating layer forming composition is curable, it may be an uncured or semi-cured product of the curable surface coating layer forming composition. If an uncured or semi-cured product of the surface coating layer forming composition is formed on the buffer layer, the surface coating layer forming composition is then subjected to a process to fully cure it. Alternatively, the buffer layer formation process and the surface coating layer formation process may involve first providing the surface coating layer and the buffer layer on the release sheet in that order, and then bonding the buffer layer to the surface of the substrate.

[0143] When the buffer layer forming composition contains an energy ray polymerizable compound, the buffer layer forming step preferably includes a step of irradiating the buffer layer forming composition with energy rays. If the buffer layer forming composition contains an energy ray polymerizable compound, the curing treatment by energy ray irradiation may be performed in a single step or in multiple steps. When performing the curing treatment by energy ray irradiation in a single step, a coating film of the buffer layer forming composition may be formed on the substrate, and then the buffer layer forming composition may be completely cured by energy ray irradiation. Alternatively, the buffer layer forming composition may be completely cured on a release sheet, and then it may be bonded to the substrate. When the surface coating layer forming composition contains an energy ray polymerizable compound, the surface coating layer forming step preferably includes a step of irradiating the surface coating layer forming composition with energy rays. The timing of irradiating the surface coating layer forming composition with energy rays is not particularly limited and may be before or after laminating the surface coating layer forming composition onto the buffer layer or buffer layer forming composition layer. When curing the buffer layer forming composition in multiple steps, after forming a coating film of the buffer layer forming composition on the release sheet, the buffer layer forming composition may be partially cured on the release sheet without being completely cured, then bonded to a surface coating layer forming composition layer provided on the release sheet, and then completely cured by irradiating with energy rays again. If the surface coating layer forming composition contains an energy ray polymerizable compound, the surface coating layer forming composition may be cured simultaneously with the energy ray irradiation required to completely cure the buffer layer forming composition. In addition, ultraviolet light is preferred as the energy ray used for curing the buffer layer-forming composition and the surface coating layer-forming composition. When curing the buffer layer forming composition and the surface coating layer forming composition by irradiating them with energy rays, the buffer layer forming composition and the surface coating layer forming composition may be exposed to the outside, but it is preferable to irradiate them with energy rays when both sides are covered with materials such as release sheets and substrates and are not exposed to the outside.

[0144] <Uses of adhesive sheets> Examples of workpiece processing performed with the adhesive sheet of this embodiment attached include backgrinding, where the adhesive sheet is attached to one side of a semiconductor device and the other side is ground; dicing, where the adhesive sheet is attached to one side of the semiconductor device and the semiconductor device is divided into individual pieces; semiconductor device transport; and semiconductor chip pickup. Among these, the adhesive sheet of this embodiment is particularly suitable for backgrinding, and is especially suitable for backgrinding, where the adhesive sheet of this embodiment is attached to the circuit formation surface of the semiconductor wafer and the back surface of the semiconductor wafer is ground. In particular, the adhesive sheet of this embodiment has the effect of suppressing the occurrence of cracks when thinning semiconductor wafers, and is therefore suitable for processes such as pre-dicing and stealth pre-dicing.

[0145] [Manufacturing method for semiconductor devices] The method for manufacturing a semiconductor device according to this embodiment is: The semiconductor processing adhesive sheet of this embodiment is attached to the surface of a semiconductor wafer with the adhesive layer as the attachment surface, The process involves grinding the back surface of the semiconductor wafer while the surface coating layer side of the semiconductor processing adhesive sheet attached to the semiconductor wafer is fixed by a support device, This is a method for manufacturing a semiconductor device, which includes [a specific component].

[0146] Furthermore, the method for manufacturing the semiconductor device of this embodiment is A division line formation step, which is a step of forming grooves on the surface of a semiconductor wafer, or a step of forming a modified region inside the semiconductor wafer from the surface or back surface of the semiconductor wafer, After step a, or before or after step b, a sheet application step is performed in which the semiconductor processing adhesive sheet of this embodiment is applied to the surface of the semiconductor wafer with the adhesive layer as the application surface. A grinding and fragmentation step is performed in which, with the surface coating layer side of the semiconductor processing adhesive sheet attached to the semiconductor wafer fixed by a support device, the back surface of the semiconductor wafer is ground to fragment it into a plurality of semiconductor chips starting from the groove or modified region. It is preferable that the method for manufacturing a semiconductor device includes the following. Furthermore, the semiconductor device manufacturing method of this embodiment may include a peeling step, after the grinding and individualization steps, in which the semiconductor processing adhesive sheet of this embodiment is peeled off from the plurality of semiconductor chips. Furthermore, the method for manufacturing a semiconductor device having step a above corresponds to a pre-dicing method, and the method for manufacturing a semiconductor device having step b above corresponds to a stealth pre-dicing method.

[0147] Examples of semiconductor wafers used in the manufacturing method of this embodiment include silicon wafers, gallium arsenide wafers, gallium nitride wafers, silicon carbide wafers, glass wafers, and sapphire wafers. Among these, silicon wafers are preferred. Circuits such as wiring, capacitors, diodes, and transistors are typically formed on the surface of semiconductor wafers. These circuits can be formed by conventionally known methods, such as etching and lift-off methods. The thickness of a semiconductor wafer before grinding is not particularly limited, but is usually between 500 and 1,000 μm. The following describes in detail each step of the manufacturing method for the semiconductor device according to this embodiment.

[0148] <Process for forming planned division lines> The division line formation process is a process of forming grooves on the surface of a semiconductor wafer, or a process of forming a modified region inside the semiconductor wafer from the surface or back surface of the semiconductor wafer.

[0149] Step a is a process of forming grooves on the surface of the semiconductor wafer, and is performed before the adhesive sheet is attached to the surface of the semiconductor wafer. The grooves formed on the surface of the semiconductor wafer in step a are shallower than the thickness of the semiconductor wafer. After step a, the semiconductor wafer is back-ground until it reaches the grooves formed in step a, and is divided into multiple semiconductor chips. Therefore, in step a, the grooves are formed along the division lines when the semiconductor wafer is divided and separated into individual semiconductor chips. Groove formation can be performed by dicing using conventionally known wafer dicing equipment, etc.

[0150] Step b is a step of forming a modified region inside the semiconductor wafer from the surface or back surface of the semiconductor wafer, and may be performed before or after attaching the adhesive sheet to the surface of the semiconductor wafer. In step b, the modified region is formed inside the semiconductor wafer by irradiation with a laser focused on the interior of the semiconductor wafer. This modified region is a brittle part of the semiconductor wafer that is broken down by back grinding, which thins the semiconductor wafer or by the force applied during grinding, and serves as the starting point for fragmentation into semiconductor chips. Therefore, the modified region is formed along the division line when the semiconductor wafer is divided and fragmented into semiconductor chips. Laser irradiation may be performed from either the front or back side of the semiconductor wafer. If step b is performed after the sheet attachment process, the laser may be irradiated onto the semiconductor wafer via the adhesive sheet.

[0151] <Sheet application process> The sheet application process is a process in which an adhesive sheet is applied to the surface of a semiconductor wafer, with the adhesive layer facing the application surface, after process a, or before or after process b. The method of attaching the adhesive sheet is not particularly limited; for example, conventionally known methods such as using a laminator can be applied.

[0152] <Grinding and framing process> The grinding and fragmentation process involves grinding the back surface of a semiconductor wafer while the surface coating layer side of an adhesive sheet attached to the semiconductor wafer is fixed by a support device, thereby fragmenting the wafer into multiple semiconductor chips starting from the grooves or modified regions. A semiconductor wafer to which an adhesive sheet has been attached and to which grooves or modified regions have been formed is fixed by a support device on the surface coating layer side of the adhesive sheet. The support device is not particularly limited, but a device that holds the object to be fixed by suction, such as a chuck table, is preferred.

[0153] Next, the back surface of the fixed semiconductor wafer is ground to separate the semiconductor wafer into multiple semiconductor chips. Backside grinding involves grinding the semiconductor wafer until the grinding surface reaches at least the bottom of the groove, provided that grooves have been formed in the semiconductor wafer by step a. This backside grinding transforms the grooves into cuts that penetrate the wafer, dividing the semiconductor wafer into individual semiconductor chips. On the other hand, if a modified region is formed on the semiconductor wafer by process b, the grinding surface may reach the modified region, but it does not have to reach the modified region strictly. That is, grinding should be done up to a position close to the modified region so that the semiconductor wafer is broken down into individual semiconductor chips, starting from the modified region. For example, after grinding up to a position close to the modified region without breaking the semiconductor wafer into individual chips, a pick-up tape may be attached to the semiconductor wafer, and the semiconductor chips may be broken down into individual chips by stretching the pick-up tape.

[0154] The shape of the individual semiconductor chips may be rectangular, or it may be an elongated shape such as a rectangle. The thickness of the individual semiconductor chips is not particularly limited, but is preferably 5 to 100 μm, more preferably 7 to 70 μm, and even more preferably 10 to 45 μm. The chip size of the individual semiconductor chips is not particularly limited, but is preferably 50 mm 2 Less than, more preferably 30 mm 2 Less than 10 mm, more preferably 10 mm 2 It is less than.

[0155] <Peeling process> The peeling process is a step in which adhesive sheets are peeled off from multiple semiconductor chips after the grinding and individualization processes. When the adhesive layer of an adhesive sheet is formed from an energy-ray curable adhesive, the adhesive is cured by irradiating it with energy rays to reduce the peeling force of the adhesive layer before the adhesive sheet is peeled off. Furthermore, when peeling off the adhesive sheet, a pickup tape may be used. The pickup tape is, for example, composed of an adhesive sheet having a base material and an adhesive layer provided on one side of the base material. When using pickup tape, first, the pickup tape is attached to the back side of the individual semiconductor wafers, and its position and orientation are adjusted so that it can be picked up. At this time, it is preferable to also attach the ring frame, which is placed on the outer periphery of the semiconductor wafer, to the pickup tape, and fix the outer edge of the pickup tape to the ring frame. Next, the adhesive sheet is peeled off from the multiple semiconductor chips fixed on the pickup tape. Subsequently, multiple semiconductor chips on the pickup tape may be picked up and then fixed onto a substrate or the like to manufacture a semiconductor device. [Examples]

[0156] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. The methods for measuring and evaluating various physical properties are as follows.

[0157] [Mass average molecular weight (Mw)] The mass-average molecular weight (Mw) was measured using a gel permeation chromatograph (Tosoh Corporation, product name "HLC-8220") under the following conditions and determined on a standard polystyrene basis. (Measurement conditions) • Columns: "TSK guard column HXL-H", "TSK gel GMHXL (x2)", "TSK gel G2000HXL" (all manufactured by Tosoh Corporation) Column temperature: 40°C • Developing solvent: tetrahydrofuran ·Flow rate: 1.0mL / min

[0158] [Measuring the thickness of adhesive sheets, etc.] The total thickness of the adhesive sheet, the thickness of each layer, and the thickness of the test specimens made from them were measured using a constant-pressure thickness measuring instrument (manufactured by Teclock Co., Ltd., product name "PG-02"). Ten arbitrary points were measured, and the average value was calculated. The total thickness of the adhesive sheet is calculated by measuring the thickness of the adhesive sheet with the release liner and subtracting the thickness of the release liner from that thickness. Furthermore, the thickness of the buffer layer is the value obtained by subtracting the thickness of the base material from the thickness of the base material with the buffer layer attached. Furthermore, the thickness of the surface coating layer is the value obtained by subtracting the thickness of the release sheet from the thickness of the surface coating layer with the release sheet attached. Furthermore, the thickness of the adhesive layer is the total thickness of the adhesive sheet minus the thickness of the surface coating layer, buffer layer, and substrate.

[0159] [Measurement of static friction coefficient] The static friction coefficient of the surface coating layer of the adhesive sheet was measured in accordance with JIS K 7125:1999 using the following procedure. The adhesive sheets manufactured in the examples and comparative examples were cut to 63 mm x 63 mm, and the release sheet on the surface coating layer was peeled off to form a sliding piece. A weight (mass 1,000 g) having the same shape as the sliding piece was attached to the adhesive layer of the sliding piece with this side facing the adhesive surface, and then placed on a SUS304 #600 steel plate so that the surface coating layer of the sliding piece was the contact surface. Next, the weight was pulled horizontally at a speed of 100 mm / min, and the static friction coefficient was calculated from the maximum load under tension. The test was conducted in an environment of 23°C and 50% RH humidity.

[0160] [Measurement of the water contact angle of the surface coating layer] The water contact angle of the surface coating layer was measured in accordance with JIS R 3257:1999. Specifically, the release sheet on the surface coating layer side of the adhesive sheets manufactured in the examples and comparative examples was peeled off, and the static contact angle when purified water was dropped onto the exposed surface of the surface coating layer was measured using a fully automatic contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., product name "DM-701") under the following conditions. ·Measurement temperature: 23℃ • Droplet volume of purified water: 2 μl ·Measurement time: 1 second after dropping • Image analysis method: θ / 2 method

[0161] [Evaluation of the amount of grinding debris adhering to the surface coating layer] Test specimens were prepared by cutting the adhesive sheets manufactured in the examples and comparative examples into 5 cm squares and peeling off the release sheet on the surface coating layer side to expose the surface coating layer. The test specimen was suspended by fixing any one of its four corners and immersed for 1 minute in grinding water containing 2% by mass of silicon wafer grinding debris. The test specimen was removed from the grinding water and allowed to dry at 23°C for 24 hours while still suspended. The surface coating layer of the test specimen was then visually inspected, and the amount of grinding debris attached was evaluated according to the following criteria. In the following evaluation criteria, "grinding debris attachment area" refers to island-shaped areas of grinding debris attachment formed by the drying of droplets of grinding water that adhered to the surface coating layer. A: There is one area on the surface coating layer where grinding debris is attached, or there is no grinding debris attached to the area that can be identified as a grinding debris attachment site. B: There are two or more areas on the surface coating layer where grinding debris is attached.

[0162] [Evaluation of transportability] The adhesive sheets produced in the examples and comparative examples were attached to a silicon mirror wafer (12 inches in diameter, 50 μm thick, dry polished finish) with the adhesive layer facing the attachment surface to produce a silicon mirror wafer with an adhesive sheet (hereinafter also referred to as "wafer with adhesive sheet"). The wafer with the adhesive sheet attached was peeled off the release sheet from the surface coating layer and placed on a heating table with the surface coating layer facing the contact surface, and heated at 80°C for 3 minutes. Then, the suction surface of a transport arm equipped with a suction mechanism was placed on the silicon mirror wafer side of the wafer with the adhesive sheet attached, and a test was conducted to see if the wafer with the adhesive sheet attached could be lifted from the heating table while the wafer with the adhesive sheet attached was suction-adhered to the suction surface, and the transportability was evaluated according to the following criteria. A: The conveyor arm was able to lift the wafer with the adhesive sheet attached from the heating table. B: The wafer with the adhesive sheet stuck to the heating table, and the transport arm was unable to lift the wafer with the adhesive sheet from the heating table.

[0163] [Preparation of urethane acrylate oligomers used in buffer layers] Manufacturing Example 1 A terminal isocyanate urethane prepolymer obtained by reacting a polyester diol with isophorone diisocyanate was reacted with 2-hydroxyethyl acrylate to obtain a bifunctional urethane acrylate oligomer with a mass-average molecular weight (Mw) of 5,000.

[0164] [Preparation of energy-curable acrylic resin for use in the adhesive layer] Manufacturing Example 2 An acrylic polymer was obtained by copolymerizing 52 parts by mass of n-butyl acrylate, 20 parts by mass of methyl methacrylate, and 28 parts by mass of 2-hydroxyethyl acrylate. Next, 2-methacryloyloxyethyl isocyanate was reacted to the acrylic polymer so as to add to 90 mol% of the total hydroxyl groups, thereby obtaining an energy-ray curable acrylic resin with a mass-average molecular weight (Mw) of 500,000.

[0165] [Manufacturing of adhesive sheets] Examples 1-10, Comparative Example 1 Next, adhesive sheets were manufactured using the method described below. Note that all amounts of each component mentioned in the following explanation refer to the amounts of the active ingredients.

[0166] (1) Preparation of the base material A polyethylene terephthalate film with a thickness of 50 μm (Young's modulus: 2,500 MPa) was prepared as the base material.

[0167] (2) Preparation of composition for forming surface coating layer Each component shown in Table 1 was dissolved in toluene to an active ingredient concentration of 10% by mass to form a surface coating layer.

[0168] (3) Preparation of buffer layer forming composition 40 parts by mass of the urethane acrylate oligomer obtained in Production Example 1, 40 parts by mass of isobornyl acrylate, 20 parts by mass of 2-hydroxy-3-phenoxypropyl acrylate, 2.0 parts by mass of 1-hydroxycyclohexyl phenyl ketone as a photopolymerization initiator, and 0.2 parts by mass of a phthalocyanine pigment were blended to prepare a composition for forming a buffer layer.

[0169] (4) Preparation of pressure-sensitive adhesive composition 100 parts by mass of the energy ray-curable acrylic resin obtained in Production Example 2, 6 parts by mass of a polyfunctional urethane acrylate which is an energy ray-curable compound (manufactured by Mitsubishi Chemical Corporation, trade name "Shikoh UT-4332", mass average molecular weight (Mw) 4,700), 0.375 parts by mass of an isocyanate-based crosslinking agent (manufactured by Tosoh Corporation, trade name "Coronate L"), and 1 part by mass of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide as a photopolymerization initiator were blended, and the mixture was diluted with an organic solvent to prepare a pressure-sensitive adhesive composition.

[0170] (5) Production of pressure-sensitive adhesive sheet The composition for forming a buffer layer obtained above was applied to one surface of the base material shown earlier so that the thickness of the buffer layer to be formed was 13 μm, followed by an illuminance of 30 mW / cm 2 and an irradiation dose of 60 mJ / cm 2 The composition for forming a buffer layer was semi-cured by irradiating ultraviolet rays under the above conditions, thereby forming a layer obtained by semi-curing the composition for forming a buffer layer on one surface of the base material. Further, the composition for forming a surface coat layer obtained above was applied to the release-treated surface of a release sheet (manufactured by Lintec Corporation, trade name "SP-PET381031") with a Meyer bar so that the thickness after drying was 2 μm, followed by heating and drying to produce a surface coat layer with a release sheet. After bonding the surface coat layer of the surface coat layer with a release sheet and the layer obtained by semi-curing the composition for forming a buffer layer formed on one surface of the base material, an illuminance of 160 mW / cm 2 and an irradiation dose of 500 mJ / cm 2By irradiating with ultraviolet light under these conditions, the buffer layer-forming composition and the surface coating layer-forming composition were cured, and a laminate having the buffer layer and the surface coating layer in that order was obtained on one surface of the substrate. Furthermore, the adhesive composition obtained above was applied to the release surface of a release sheet (Lintec Corporation, product name "SP-PET381031") so that the thickness after drying was 20 μm, and then heated and dried to produce a release sheet with an adhesive layer. By attaching the adhesive layer of the release sheet with the adhesive layer to the surface of the substrate of the laminate that does not have a buffer layer, an adhesive sheet having a surface coating layer, a buffer layer, a substrate, and an adhesive layer in that order was obtained.

[0171] Table 1 shows the evaluation results obtained using the adhesive sheets from each example and comparative example.

[0172] [Table 1]

[0173] • H1043: Hydrogenated styrene-based thermoplastic elastomer (SEBS), styrene content: 67% by mass, manufactured by Asahi Kasei Corporation, product name "ToughTec (registered trademark) H1043" • PMA-L: Propylene-butene-maleic anhydride copolymer, maleic anhydride modification rate: 1.5% by mass, mass-average molecular weight (Mw): 75,000, manufactured by Toyobo Co., Ltd., product name "Toyo Tack (registered trademark) PMA-L"

[0174] • X-22-164B: A polydimethylsiloxane compound having methacryloyloxy groups at both ends, mass-average molecular weight (Mw): 5,000, manufactured by Shin-Etsu Chemical Co., Ltd., trade name "X-22-164B". • X-22-164E: A polydimethylsiloxane compound having methacryloyloxy groups at both ends, mass-average molecular weight (Mw): 13,000, manufactured by Shin-Etsu Chemical Co., Ltd., trade name "X-22-164E".

[0175] • Energy-ray polymerizable polyfunctional compound: A mixture of dipentaerythritol hexaacrylate and dipentaerythritol pentaacrylate, manufactured by Nippon Kayaku Co., Ltd., trade name "KAYARAD DPHA" • Photopolymerization initiator: 2-hydroxy-2-methyl-1-phenylpropanone, manufactured by IGM Resins BV, trade name "Omnirad1173"

[0176] Table 1 shows that the adhesive sheets of Examples 1 to 10, which have a surface coating layer with a static friction coefficient of 0.70 or less, exhibit excellent transportability and significantly reduce the amount of grinding debris adhering to them. On the other hand, the adhesive sheet of Comparative Example 1, which has a surface coating layer with a static friction coefficient exceeding 0.70, had poor transportability and more grinding debris adhering to it than the adhesive sheets of Examples 1 to 10.

Claims

1. The surface coating layer, buffer layer, substrate, and adhesive layer are provided in this order. The surface coating layer has a static friction coefficient of 0.70 or less with respect to SUS304. The thickness of the surface coating layer is 0.05 to 7 μm. An adhesive sheet for semiconductor processing, wherein the buffer layer is formed from a buffer layer forming composition containing urethane (meth)acrylate.

2. The semiconductor processing adhesive sheet according to claim 1, wherein the surface coating layer is formed from a surface coating layer forming composition containing a resin component and a slipperiness improving component.

3. The adhesive sheet for semiconductor processing according to claim 2, wherein the resin component has a heteroatom content of 7% by mass or less.

4. The semiconductor processing adhesive sheet according to claim 2, wherein the content of the resin component in the surface coating layer forming composition is 50 to 99% by mass relative to the total amount (100% by mass) of the active ingredients of the surface coating layer forming composition.

5. The adhesive sheet for semiconductor processing according to claim 2, wherein the slipperiness-improving component contains 30% by mass or more of heteroatoms.

6. The semiconductor processing adhesive sheet according to claim 2, wherein the content of the slipperiness-improving component in the surface coating layer forming composition is 0.1 to 30% by mass relative to the total amount (100% by mass) of the active ingredients in the surface coating layer forming composition.

7. An adhesive sheet for semiconductor processing according to claim 1 or 2, used for grinding the back surface of a semiconductor wafer.

8. A step of attaching the semiconductor processing adhesive sheet according to claim 1 or 2 to the surface of a semiconductor wafer with the adhesive layer as the attachment surface, The process involves grinding the back surface of the semiconductor wafer while the surface coating layer side of the semiconductor processing adhesive sheet attached to the semiconductor wafer is fixed by a support device, A method for manufacturing a semiconductor device, including the method described above.

9. A division line formation step, which is a step of forming grooves on the surface of a semiconductor wafer, or a step of forming a modified region inside the semiconductor wafer from the surface or back surface of the semiconductor wafer, A sheet application step is performed after step a, or before or after step b, by applying the semiconductor processing adhesive sheet according to claim 1 or 2 to the surface of the semiconductor wafer with the adhesive layer as the application surface. A grinding and fragmentation step is performed in which, with the surface coating layer side of the semiconductor processing adhesive sheet attached to the semiconductor wafer fixed by a support device, the back surface of the semiconductor wafer is ground to fragment it into a plurality of semiconductor chips starting from the groove or modified region. A method for manufacturing a semiconductor device, including the method described above.

Citation Information

Patent Citations

  • Substrate for adhesive tape, adhesive tape and adhesive tape with release tape

    JP1999189755A

  • Base material for wafer dicing tape

    JP2003158098A

  • Adhesive tape for protection of semiconductor wafer surface and method for processing semiconductor wafer

    JP2015056446A

  • Pressure-sensitive adhesive sheet, and method of manufacturing semiconductor chip or semiconductor component using the same

    JP2018129491A

  • Film, sheet substrate for processing workpiece, and sheet for processing workpiece

    WO2013141251A1